ANALISA PERANCANGAN SERVER VOIP (VOICE INTERNET PROTOCOL) DENGAN OPENSOURCE ASTERISK DAN VPN (VIRTUAL PRIVATE NETWORK) SEBAGAI PENGAMAN JARINGAN ANTAR CLIENT - Domiko Fahdi Jaya Patih (Universitas Lampung, 2013)
Abstrack Voice over Internet Protocol (VoIP) is a technology that utilizes the Internet Protocol to provide real-time voice communication. VoIP technology is a today telecommunication technology, where the costs of the technology infrastructure is much cheaper than the telecommunications technology that is commonly used today. Forming elements are VoIP User Agent, Proxy, Protocol and Coder-Decoder (CODEC). Asterisk is a softswicth to operate a proxy, which is based on session initiation protocol (SIP). 10.10 Ubuntu operating system as a VoIP server is flexible to support a package of performance Asterisk. The goal of this research is to build Asterisk-based VoIP server, that can be developed in further research as needed. The methodology of research conducted, is devided by two, the study of literature and experimental. The research was conducted at the installation that has been built before the Internet network. VoIP so here functioned as maximizing existing internet network is to reduce expenses communication needs. Services provided in this study form with voice and video call services client to server, client to client call, video call conferencing, video conferencingKey Word : Voice over Internet Protocol (VoIP), Asterisk, Session Initiaton Protocol (SIP), VPN